Suspended graphene-based NEMS accelerometers with direct electrical readout - Jie Ding; Chang He; Hongliang Ma; Wendong Zhang; Xuge Fan (Microsystems & Nanoengineering)
Abstract Atomically thin suspended graphene can be used as NEMS transducers for ultra-small and high-performance sensors due to its excellent mechanical and electrical properties. Most applications of suspended graphene in NEMS devices are limited to pressure sensors, resonators, switches, etc. Graphene-based NEMS accelerometers have rarely been reported, with limitations such as mechanical robustness, life span and device yield, thereby limiting their practical applications. Here, we reported piezoresistive graphene-based NEMS accelerometers with high manufacturing yield, excellent mechanical robustness and stability, and long life span, in which the width of trenches for suspending graphene membranes was only 1 µm and fully-clamped suspended double-layer graphene membranes with an attached SiO2/Si proof mass was used as acceleration transducer. The impact of geometrical sizes of the proof mass attached to the suspended graphene membranes on the output signal of devices has been studied. These findings would contribute to rapid developments and practical applications of ultra-small and high-performance graphene-based NEMS accelerometers and related devices.